RESPON PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomea reptans Poir.) DENGAN AKIBAT PENAMBAHAN PUPUK ECO FARMING - Ani, Sherly; M. Idris; Rahmadina (Jurnal Biogenerasi, 2025)
Efforts to increase water spinach production in the future still and continuously rely on improving soil fertility and the use of effective and efficient media. Fertilizers used for water spinach plants can be organic or inorganic fertilizers. Continuous use of inorganic fertilizers has a negative impact on soil productivity. Therefore, the use of environmentally friendly fertilizers in cultivating land water spinach is urgently needed, for example the use of organic fertilizers. Eco Farming fertilizer is an organic fertilizer produced with the aim of increasing plant productivity by improving agricultural soil texture. The purpose of this study was to determine how much concentration of Eco Farming fertilizer should be given to land water spinach plants. This research was conducted from June - July 2023 at the State Islamic University of North Sumatra, Jln. Golf Course, Durian Jangak Village, Pancur District, this research used quantitative experiments. This study used a Randomized Block Design, Non Factorial, namely the dose (P0 = control; P1 = 7.5 ml eco farming; P2 = 15 ml eco farming; P3 = 22.5 ml eco farming. This had a significant impact on plant height parameters, and the P2 dose was the most effective according to research findings